An experimental investigation on performance and emission parameters of a multi-cylinder SI engine with gasoline–LPG dual fuel mode of operation. Issue 1 (2nd January 2017) - Nayak, Vighnesha; Shankar, K. S.; Dinesha, P.; Mohanan, P.
ABSTRACT: The present study deals with the performance and emission characteristics of a multi-point fuel injection (MPFI) spark ignition (SI) engine in gasoline–liquefied petroleum gas (LPG) dual fuel mode of operation. The LPG–gasoline ratio varied from 0 to 100% by controlling the injector signals at various speed and load conditions. Experiments show that the power output decreases with increase in speed and LPG content at lower load marginally due to lower volumetric efficiency. At higher load and lower speed conditions as the percentage of LPG increases there is not much difference in the power output. Results also reveal that 50% LPG flow gives maximum efficiency at full load condition and 4000 rpm due to lower fuel consumption. With 50% usage of LPG, the average increase in brake thermal efficiency (BTE) is 2% till the engine speed of 4000 rpm at full load (100%) and half load (50%) conditions. As the LPG ratio increases the engine will work in the lean region for all speed and load conditions. For all load and speed conditions, results reveal that 100% LPG will give minimum hydrocarbon (HC) and carbon monoxide (CO) emissions. Oxide of nitrogen (NOX ) emissions are higher for 100% LPG. However 50% LPG flow gives good agreement of NOX, HC and CO emissions when compared with gasoline operation.